Distribution of intestinal parasite in people garbage collecing and street sweeping community in Bhaktapur, Nepal. - Simkhada,Dhruba (2015)
ABSTRACT: Intestinal parasitic infections are globally endemic and have been described as constituting one of the major worldwide causes of illness and disease. The study was conducted in order to find out the prevalence of parasites in people residing in Belukhel, Bhaktapur from March 2014 to November 2014. A total 510 samples were taken for the study. Single stool specimens were processed for each study subject. The samples were examined for intestinal parasites using a normal saline, iodine preparation and concentration method. The overall parasitic infection was found to be 20.98% i.e. out of total 510 processed sample 107 were found to be positive. Out of total 510 processed samples 308 (60.39%) were of male samples and 202 (39.61) were of female samples. In the parasitological examination 47(23.27) female samples were positive and 60 (19.48%) male samples were positive. Among the parasites Entamoeba histolytica was observed in 29 cases. This constituted 5.69% of total processed sample and 27.105 of total parasites found. Giardia Lambia 23(21.49%), E. coli 7(6.54%), Cyclospora cayetanesis 5 (4.67) and among helminthes Ascaris lumbricoides 18 (16.82) , hookworm 11 (10.28%) , Hymenolepsis nana 7 (6.54% Trichuris trichiura 4 (3.73%) and Enterobius vermicularis 3 (2.80%). The study also showed that the people who are below 15 years and above 59 years are more susceptible to infection as compared to those who are age between 15 to 59. Likewise, uneducated people are more susceptible to infections as compared to educated people. Key words: Street sweepers, Garbage collectors, Intestinal parasites, Diarrhea